Some Preliminary Thoughts Prompted by President Trump's 6 January Speech: Words, Enemies, Affordances. Issue 5 (4th July 2021) - Taylor, Max
ABSTRACT: The paper argues that in order to understand the events of 6 January we must look at events from a range of perspectives, two of which are identified—the narrow focus of a comparison of a linguistic analysis of the speech and its context, and the broader social and cultural context of a changing sense of American National Interest. It suggests that to understand the events of 6 January we need to conceptualise them as the product of a complex process where both aggregate and specific influences seem relevant, but whilst both offer necessary explanations neither in themselves provide a sufficient explanation of the event. The concept of affordance is suggested to perhaps provide the glue that may bind these and other influences together to facilitate the violence.